A methods engineering study of Chris Jordan Enterprise - Ragasa, Catherine; Salazar, Faye A.; Veron Cruz, Rona Sophia K. (Diliman, Quezon City College of Engineering, 1994)
The Work Study is divided into four areas, namely : Layout Analysis, Motion Analysis, Workplace Layout and Work Measurement. As shall be seen, each of these affects to a greater or lesser extent all the other areas of study. Each forms an integrated part of the study, such that recommendations in each area will have to be implemented simultaneously in order to effect efficient results. Layout analysis deals primarily with the set-up of the whole process, including the plant layout and how the manufacturing process works. The factory, being just converted to a residence, presents some difficulties in this regard. This is because the process has to be adapted to the plant layout, which in this case is really not ideal. This also puts into peril the practice of the motion economy principles. But this, as we shall see later, are nonetheless practiced. The workplace, specifically, the assembly area of golf club covers presents the same difficulties. That is why things such as ventilation, lighting, etc. have to be carefully examined and evaluated to ensure worker efficiency. Work measurement tackles the same activity as that of the workplace layout, more specifically, the tying of the golf club covers. It is advantageous that this be so, because how much a person is able to work depends to a great extent to the workplace itself. Calculations of allowances especially induces and important effect in this regard. Thus, questions such as the strain the workplace puts on the worker, the distance of the comfort rooms, etc. all have to be included in the calculation of allowances to be given. In summary, every area of the study contributes to making the whole process more efficient. In the next pages, each of the areas will be considered separately and the corresponding recommendations given. What is important is that all the recommendations be done simultaneously.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Chris Jordan Enterprise; Factories; Systems analysis